Fragmenter af et håndværk: Ten- og vævevægte fra førromersk jernalder i Jylland - Lerke, Line; Hjorth-Jørgensen, Christine Søvsø (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
Until now, spindle whorls and loom weights from the Pre-Roman and Early Roman Iron Age in Denmark have never been studied systematically, leaving an unexploited potential of insights into Early Iron Age textile craft. These spinning and weaving tools were finally documented and investigated during our bachelor project and master’s thesis at the University of Copenhagen in 2015 and 2017. The geographical focus was set on Jutland with its many settlements and burial sites from the periods in question. The projects resulted in various conclusions, among others that the use of the warp-weighted loom is reserved for the few, as indicated by a small number of loom-weights, which also coincides with the weaving technological testimonies of the many well-preserved textiles. Based on the work of e. g. Centre for Textile Research, this article lines out how to make analytical use of a loomweight. The spindle whorls appear in much higher numbers, representing a wide range of spinning potentials. The primary type of spindle-whorl is disc-shaped and manufactured from re-used potsherds, which have been rounded and pierced from both sides. We have tested these widely debated clay objects in a spinning test, which proved to determine that uneven sherds with skew piercings may very well be used as spindle whorls and do not have a negative effect on the outcome of the thread. The focus on these humble artefacts has integrated the textile tools in a conceptual framework stretching across manufacture and function, which is widening the understanding of textile craft in the Early Iron Age.